Identification of Arcanobacterium hippocoleae by MALDI-TOF MS analysis and by various genotypical properties. (December 2017) - Wickhorst, J.-P.; Sammra, O.; Hassan, A.A.; Alssashen, M.; Lämmler, C.; Prenger-Berninghoff, E.; Erhard, M.; Metzner, M.; Paschertz, K.; Timke, M.; Abdulmawjood, A.
Abstract: In the present study an Arcanobacterium hippocoleae strain isolated from a uterus swab of an apparently healthy mare could be identified by phenotypic properties, by MALDI-TOF MS analysis and genotypically by investigating the molecular targets 16S rDNA, 16S-23S rDNA intergenic spacer region and the genes encoding the β subunit of bacterial RNA polymerase ( rpoB ), elongation factor tu ( tuf ) and glyceraldehyde 3-phosphate dehydrogenase ( gap ). The presented data are one of the few reports about the species A. hippocoleae and might help to elucidate the role this species plays in infections of horses.